2019
DOI: 10.1038/s41598-019-54055-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in meta-transcriptome of rumen epimural microbial community and liver transcriptome in young calves with feed induced acidosis

Abstract: The common management practices of dairy calves leads to increased starch concentration in feed, which subsequently may cause rumen acidosis while on milk and during weaning. Until recently, few attempts were undertaken to understand the health risks of prolonged ruminal acidosis in post weaning calves. Resultantly, the molecular changes in the digestive tracts in post-weaning calves with ruminal acidosis remain largely unexplored. In this study, we investigated the liver transcriptome changes along with its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Differential abundance analysis of microbial taxa at genus level was done using DEseq2 (with Benjamini and Hochberg method for multiple testing) using the raw read counts mapped to the given taxa ( p < 0.05; mean read count ≥10 and fold-change ≥2). For the RE tissues collected at 17 weeks of age, we used genus-level reads counts from our previously published work ( 19 ). It is known that rumen development is accompanied by microbial colonization ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Differential abundance analysis of microbial taxa at genus level was done using DEseq2 (with Benjamini and Hochberg method for multiple testing) using the raw read counts mapped to the given taxa ( p < 0.05; mean read count ≥10 and fold-change ≥2). For the RE tissues collected at 17 weeks of age, we used genus-level reads counts from our previously published work ( 19 ). It is known that rumen development is accompanied by microbial colonization ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences classified as chloroplast and mitochondria were excluded before downstream analysis. Raw-read counts at each taxonomic level (i.e., phylum and genus) were normalized per sample with the per million factor as described in [ 25 ]. Major classified taxa, defined as occupying over 0.01% average relative abundance in at least one of the treatments, were discussed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…increased ( p < 0.05) and anti-inflammatory(IL-6) ones decreased( p < 0.05), in addition, SARA will increase milk somatic cell count (SCC) with a dropped milk protein and lipid component ( p < 0.05). Li et al [ 28 , 29 ] found that young calves with high starch induced rumen acidosis performs a different rumen epithelial transcriptome and meta-trascriptome profile with correlated rumen microbiome, liver transcriptome pattern also involved in this process, the abundance of Olsenella , Desulfovibri , and Fusobacterium necrophorum increased significantly in the rumen fluid, and 95 genes in the liver changed with differed microbiome rRNA expression, among them, 77 genes are enriched in the pathways of membrane-bounded organelle and transferase activity. Six-hundred-and-seventy-two epithelial genes related to cell signaling and morphogenesis showed significantly altered expression, in which, 12 genes ( COX5B , KRT78 , KRT15 , ATP5I , ATP5L , ATP5G2 , COX8B , COX8A , UBC , DSP , ITM2B , and C10H15orf48 ) related to hydrogen ion transmembrane transport only exists in the acidosis group; other differentially expressed genes are mostly involved in cell division and growth, like membrane-bounded organelle, cytoplasm, cellular component organization or biogenesis.…”
Section: Multi-omics Promotes Revealing Dairy Diseasesmentioning
confidence: 99%